Coronary artery atherosclerosis in reproductive age group women-an autopsy study - Chaithra R Jadhav; Fremingston Marak; Bharathi Pradeep (Asian Journal of Medical Sciences, 2024)
Background: Atherosclerosis is the most common coronary artery disease (CAD). It leads to the blocking of arteries and myocardial infarction (MI). Many studies are focused on men. The aim of this study is to look at the prevalence of coronary atherosclerosis, its severity, and arteries involved in postmortem hearts in reproductive age group women. Aims and Objectives: The objectives are (1) to estimate the occurrence of coronary atherosclerosis in reproductive age group women of 15–50 years. (2) To grade the atherosclerosis and stenosis. (3) To determine the cardiac changes associated. (4) To note the most common artery involved. Materials and Methods: This study was autopsy-based retrospective study done for period of 3 years. From the autopsy forms, details such as age, gender, cause of death, and gross findings were noted. The sections from the left coronary artery (LCA), right coronary artery, left anterior descending (LAD), and circumflex artery (LCA) were reviewed microscopically to note the atherosclerotic grade and percentage of stenosis. Myocardium was reviewed for associated cardiac changes. Range, frequencies, percentage, and P-value were calculated. P<0.05 was taken statistically significant. Results: Eighty-seven cases belonging to the reproductive age group of 15–50 years were categorized into 4 age groups. Type V American Heart Association atherosclerosis grade was seen more in women between 35 and 50 years. LAD was the most common artery to be involved. Eight cases showed acute MI. Conclusions: Women of reproductive age group should be screened from 3rd decade onwards for CAD.